The Effect of Using Fartlek Training Method on Developing Speed, Strength Endurance, and Court Defense Skill Performance in Volleyball - Ali Hameed Ali Al-Zubaidi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The study aimed to design a training program using the Fartlek training method to develop speed and strength endurance among preparatory school students, as well as to investigate the impact of Fartlek training on improving the technical performance of court defense skills in volleyball. The researcher adopted the experimental method with pre- and post-test measurements. The sample was selected purposively and consisted of volleyball players, specifically 18 second-year students. Six students were excluded for participating in the pilot experiment, leaving 12 students as the final research sample. The Statistical Package for the Social Sciences (SPSS)، was used to analyze the results. The findings revealed statistically significant differences between the pre- and post-tests in favor of the post-test. The progressive application of exercises positively contributed to the development of both physical and skill-related variables. The researcher recommended emphasizing physical and skill-related variables due to their importance in enhancing player performance. Additionally, the study advocated for implementing the training program—with its physical and skill-focused exercises—in regular training sessions, given its effectiveness in improving all tested parameters. The use of the Fartlek training method in training units was also encouraged, as it proved impactful in developing the physical capacities of the sample.